INTERDISCIPLINARY LINKS IN THE FORMING OF METHODICAL COMPETENCE OF FUTURE MUSIC TEACHERS - Teriaieva, Larysa A. (Educological discourse, 2015)
Article is devoted to the formation of methodical competence of future music teachers through the use of interdisciplinary connections in the study of discipline «Choral Conducting». By sharing information and interdisciplinary integrated communication deepened, summarizes the knowledge and skills both in choral conducting, and related disciplines that promotes the formation of methodical competence of future teachers of music. Study materials are the basis for an adjustment in the content of the curriculum and updating on the basis of interdisciplinary connections, as well as for optimizing the learning process with choral conducting training.